"Finally, we get to play the doctor": feminist female fans' reactions to the first female Doctor Who. Issue 8 (16th November 2020) - Yodovich, Neta
ABSTRACT: This paper offers an exploration into feminist female fans' reactions to the first female Doctor ( Doctor Who 's protagonist). After 55 years of male actors, the 13th Doctor became a woman in 2017. The announcement was met with a backlash, especially from male fans. Unlike previous studies on controversial casting, which focused on the negative commentators, this study sheds light on the supporters who defend the casting while being personally attacked. This research is based on 22 semi-structured in-depth interviews with self-identified feminist female fans of Doctor Who, a minority in a fandom that is perceived as male-dominated. Interviews were conducted after the announcement and before the airing of the new series. This timing provided the opportunity for participants to project their expectations onto the new Doctor. The findings reveal ambivalent reactions: interviewees avidly defended the casting and considered it an important step towards gender equality, both in popular culture and outside of it. However, they also wished the female Doctor would maintain masculine characteristics. This article offers first-hand accounts of feminist female fans who feel excluded from their fan community and the object of their fandom, and the tactics they employ to defend themselves and the new female leading character.